2017
DOI: 10.3389/fped.2017.00013
|View full text |Cite
|
Sign up to set email alerts
|

Results of Late Gadolinium Enhancement in Children Affected by Dilated Cardiomyopathy

Abstract: BackgroundLittle is known about the clinical value of late gadolinium enhancement (LGE), in children affected by dilated cardiomyopathy (DCM).Materials and methodsWe retrospectively evaluated 15 patients (8 ± 6 years, 6 males) with diagnosis of DCM who underwent cardiac magnetic resonance since 2014. All scans were performed with a 1.5 T system (Aera, Siemens). Study protocol included cine steady-state free precession sequences, followed by administration of 0.2 mmol/kg of gadolinium-based contrast agent. Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Cardiac output and ejection fraction reduced from healthy values to the values characterized as impaired [72,73]. The left ventricular volume signal over a cardiac cycle increased as a result of dilatation and cause dilation in the left atrial volume, as reported in [74]. Left ventricular end-diastolic and end-systolic diameters and right ventricular diameter were similar to patient-specific values reported in [73] and remained within the reported range in the children for the studied age interval [75].…”
Section: Discussionmentioning
confidence: 87%
“…Cardiac output and ejection fraction reduced from healthy values to the values characterized as impaired [72,73]. The left ventricular volume signal over a cardiac cycle increased as a result of dilatation and cause dilation in the left atrial volume, as reported in [74]. Left ventricular end-diastolic and end-systolic diameters and right ventricular diameter were similar to patient-specific values reported in [73] and remained within the reported range in the children for the studied age interval [75].…”
Section: Discussionmentioning
confidence: 87%
“…The findings of our study are comparable with previously published reports on adults with DCM in whom LGE was detected with a frequency of up to 39%, while others described lower presence of LGE ( 2 5 ). Data on LGE in children and adolescents with DCM are sparse ( 21 , 22 ). In the study by Latus et al, LGE was present in only 16% of the pediatric DCM cohort despite marked LV dilation and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Muscogiuri found LGE in 47% of children with DCM. In all patients, LGE occurred in a global diffuse subendocardial pattern compatible with primary endocardial fibroelastosis, and was associated with reduced global LV systolic function ( 22 ). In line with these data, it has been shown that LGE is related to functional impairment ( 23 ), and is a predictor of arrhythmias, cardiovascular hospitalization and death in adult DCM ( 2 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…CMR studies for pediatric DCM have focused on the early detection of myocardial involvement in children at high risk for developing ventricular dysfunction, such as muscular dystrophy patients [23][24][25] and pediatric cancer survivors exposed to anthracyclines and radiation [26,27]. Myocardial fibrosis demonstrated by LGE was seen in association with ventricular dysfunction in the DCM or muscular dystrophy group [28][29][30], but not in the pediatric cancer survivor group [27,31]. In a study of long-term survivors of childhood leukemia, LGE was associated with LV and right ventricular (RV) diastolic dysfunction [32].…”
Section: Dilated Cardiomyopathy and Post-chemotherapy Cardiomyopathymentioning
confidence: 99%